Ayurvedic approach to psychosomatic distress due to COVID-19 - Sheenam Gangawat; Shamsa Fiaz (Wolters Kluwer Medknow Publications, 2020)
Introduction: The outbreak of COVID-19 came into existence last year in December 2019 at Wuhan, China. The WHO declared it as pandemic and great threat to the humanity. The Government of India has taken various steps to prevent the citizens such as lockdown, work from home, guidelines for social distancing, and screening. Due to which, the disease has been controlled to a great extent, but it has also seen very terrible results such as loss of business of a large number of people and health services collapsed which leads to socioeconomic insecurity in society results to psychosomatic distress. Objective: The objective was to understand the role of Ayurveda for overcoming the psychosomatic distress due to COVID-19. Materials and Methods: Psychosomatic distress causes were analyzed by the data given in various private and government reports available in the public domain through their official websites, journals, newspapers, and magazines. Figure out the best possible preventive and Ayurvedic principles from different Samhitas and textbooks for psychosomatic distress. Conclusion: At a time where none of the medical systems of the world have any authentic treatment for COVID-19, Ayurveda is the most appropriate and safe medical practice for the people of India because it is time-tested and cost-effective. With the help of Ayurveda, we can avoid corona by increasing immunity following dincharya, ritucharya, and aachar rasayan. Thus, we can save ourselves and our family from the side effects caused by COVID-19.